PENGARUH PENGGUNAAN MEDIA SIMULASI PHET TERHADAP MINAT DAN HASIL BELAJAR SISWA KELAS XI SMAK SYURADIKARA - Lepu, Maria Kaspriani; Daud, Maimunah Haji; Lidi, Maria Waldetrudis (Borneo Journal of Biology Education (BJBE), 2024)
This research aims to determine the impact of using PhET simulation media on the interest and learning outcomes of Grade XI SMAK Syuradikara students. This type of research is a quantitative experimental study with a non-equivalent control group design. The subjects of this study are 291 students of class XI and the research sample of 66 students was taken using probability sampling technique with simple random sampling. Data analysis was performed by t-test using the SPSS 20.0 program for Windows. The research results show that the value of the question about students' learning interest is 88.02 and the results of testing the hypothesis about students' learning interest show that the t-test value is 23.477 1.696. Meanwhile, cognitive learning outcomes after treatment increased by 86.71. The student's emotional learning outcome after treatment was 97.72. The psychomotor learning result after treatment was 96.22. Testing the hypothesis about student learning outcomes shows that the t-test value is 35.670 1.696, so H1 = accepted. Based on the results of the study, it can be concluded that the use of PhET simulation media affects the interest and learning outcomes of Grade XI SMAK Syuradikara students.